Use of Instagram as a Medium for Adolescence Self-Identity Construction - Aulia, Farah; Putri, Kinkin Yuliaty Subarsa (UIR Press, 2024)
As social creatures, humans have a need to interact and communicate with others. Humans have many ideas, ideas, opinions, that need to be conveyed to meet their needs. Communication becomes a bridge that becomes a link in delivering messages so as to form understanding. In the era of rapidly developing technology, the face of communication has undergone a significant evolution. Communication can not only be done face-to-face, but now it can be through social media intermediaries. Instagram is a social media with many users in Indonesia. Instagram has advantages that can attract adolescents, so adolescents are active Instagram users. Through its use, Instagram can be a medium of self-identity construction. Adolescence is a period of searching for self-identity. Instagram users, especially adolescents, tend to share photos and videos that can represent themselves in front of an audience. This study discusses the use of Instagram as a medium of self-identity construction for adolescents. The subjects of this study were adolescents with an age limit of 19 years and domiciled in Jakarta. This research uses a quantitative approach with data collection techniques in the form of surveys. The results showed that Instagram is effective in the formation of self-identity through the consistency of content and narratives made according to self-representation.